Fundamentals of Enzyme Engineering - Yoo, Young Je; Feng, Yan; Kim, Yong-Hwan; Yagonia, Camila Flor J. (Springer Netherlands : Imprint: Springer, 2017)
This book provides a comprehensive introduction to all aspects of enzyme engineering, from fundamental principles through to the state-of-the-art in research and industrial applications. It begins with a brief history, describing the milestones of advancement in enzyme science and technology, before going on to cover the fundamentals of enzyme chemistry, the biosynthesis of enzymes and their production. Enzyme stability and the reaction kinetics during enzymatic reactions are presented to show how enzymes function during catalysis and the factors that affect their activity. Methods to improve enzyme performance are also presented, such as cofactor regeneration and enzyme immobilization. The book emphasizes and elaborates on the performance and characteristics of enzymes at the molecular level. Finally, the book presents recent advances in enzyme engineering and some key industrial application of enzymes addressing the present needs of society. This book presents essential information not only for undergraduate and graduate students, but also for researchers in academia and industry, providing a valuable reference for the development of commercial applications of enzyme technology.